(untitled) (Scientific journal of the Fergana State University, 2024)
In the article, the Fergana Valley is an important region in the demographic processes of Uzbekistan, the standard of living of the population, family, marriage, divorce, maternal mortality, female mortality, infant and child mortality. The political reforms carried out in Uzbekistan over the years of independence are becoming increasingly important in the development of the republic, especially in the Fergana Valley. In this regard, a socio-philosophical analysis of the impact of political reforms in the economic and social spheres carried out in Uzbekistan on families in the Fergana Valley was carried out.